Perspektif Ekonomi Islam Pada Jual Beli Pakaian Bekas Impor (Studi Kasus @Calamae) - Makhmudah, Khoirum; Moch. Khoirul Anwar (Jurnal Ekonomika dan Bisnis Islam, 2022)
Buying and selling clothes is a common buying and selling in society. And in recent times, buying and selling of imported used clothes has also attracted a lot of attention from the public, especially those from generation Z. This study aims to analyze the phenomenon of buying and selling imported used clothes online through an Islamic economic point of view and based on applicable laws in Indonesia. territory of the Republic of Indonesia. This research uses descriptive qualitative method. The researcher describes the mechanism of buying and selling used clothes that occurs in the @calamae account and then studied based on an Islamic economic perspective. The results of this study indicate that the buying and selling practices carried out on the @calamae account are in accordance with the terms of sale and purchase according to Islam, but if traced from the beginning the goods were obtained, there are disadvantages in them because the goods were obtained illegally and violated the export-import laws that apply in Indonesia. Indonesia.